The Relationship Between Organizational Commitment and Readiness to Change for Employee of PT X - Prastiti, Zaretta Dias (LPPM Universitas Terbuka, 2021)
The purpose of this study is to determine the relationship of organizational commitment and readiness to change. This study is a quantitative research with an explanatory method. The subject for this research conducted to 75 employee of PT X Jatimbalinusra. Data collection using Organizational Commitment Scale developed by Allen and Mayer (1991) and READ 3 Readiness for Change Scale belongs to Hanpacern (1997). Data analysis using IBM SPSS Statistic 22. From the result of this study showed the correlation between the value of organizational commitment and readiness for change is 0,000 which is worth less than the significance level of 0,05. The strenght of the correlation between two variables is strong with a value of 0,856. This indicate that there is a significant correlation between organizational commitment and readiness to change.